The Relationship Between Exclusive Breast Feeding With Fine Motoric Development In Infants 6-12 Months Of Age In The Village Kebonsari Rw 02 Temple Sidoarjo - Nisa, Fauziyatun (Journal of Global Research in Public Health, 2018)
Baby village temple Kebonsari sidoarjo many are not exclusively breastfed because most mothers so busy working impaired fine motoric development. The purpose of this study was to determine the relationship of exclusive breastfeeding with fine motoric development in infants aged 6-12 months Kebonsari Candi Sidoarjo village. This study design was observational analytic. The study population was 35 pairs of mothers and infants village temple Kebonsari Sidoarjo and sample 32 pairs of respondents, taken by simple random sampling. The independent variables were exclusively breastfed and fine motoric development of babies as the dependent variable. Instrument data collection using questionnaires and observation sheets DDST then Spearman rank test with significance level Î± = 0.05. The results showed that a large part (71.9%) of mothers breastfeeding, and the bulk (62.5%) infants have normal fine motoric development. Spearman rank test results obtained value of Ï = 0.023 <Î± = 0.05, H0 denied, there is a relationship of exclusive breastfeeding with fine motoric development in infants aged 6-12 months Kebonsari Candi Sidoarjo village. The conclusions of this research are mothers who exclusively breastfed their babies and fine motoric development is normal. Nurses are highly recommended providing information about how and benefits of exclusive breastfeeding for the stimulation of the development of fine motoric skills